2019
DOI: 10.3354/esr00992
|View full text |Cite
|
Sign up to set email alerts
|

A beacon of hope: distribution and current status of the largetooth sawfish in Costa Rica

Abstract: The Critically Endangered largetooth sawfish Pristis pristis is one of the most threatened elasmobranch species and is currently thought to be locally extinct in at least 27 countries. Although largetooth sawfish information in Central America is scarce, recent records show that this species is still present in Costa Rica, yet its distribution and current status remain unclear. This study investigated the spatial and temporal distribution of the largetooth sawfish in Costa Rica and identified local threats aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Interviewees stated that once sawfish were caught, the meat was consumed and the rostrum was cut off and kept mainly for decorative purposes or later sold to buyers looking for their teeth. In Panama, some fishers reported that the teeth were fashioned into artificial spurs used in cockfighting, as documented from Perú (Cogorno Ventura 2001), something that has been observed by the authors on online sales sites and corroborated in other studies in Latin America (McDavitt 2014, Valerio-Vargas & Espinoza 2019. In Colombia, some fishers mentioned that the meat was used for consumption, but most pointed out that the rostrum was the most valuable sawfish body part because of its decorative value.…”
Section: Discussionmentioning
confidence: 70%
“…Interviewees stated that once sawfish were caught, the meat was consumed and the rostrum was cut off and kept mainly for decorative purposes or later sold to buyers looking for their teeth. In Panama, some fishers reported that the teeth were fashioned into artificial spurs used in cockfighting, as documented from Perú (Cogorno Ventura 2001), something that has been observed by the authors on online sales sites and corroborated in other studies in Latin America (McDavitt 2014, Valerio-Vargas & Espinoza 2019. In Colombia, some fishers mentioned that the meat was used for consumption, but most pointed out that the rostrum was the most valuable sawfish body part because of its decorative value.…”
Section: Discussionmentioning
confidence: 70%
“…Elasmobranch studies in Costa Rica using fishery-independent methods have also reported similar species richness and composition compared to our study, at least at local scales (Table 4, Table S2). For example 39 , used data collected by divers over 21 years to investigate elasmobranch population trends at Cocos Island, whereas 38 analyzed video footage from submarine surveys between 2006 and 2012 to examine elasmobranch assemblages in deep waters. All the species recorded by 39 were also detected in our study (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…All the species recorded by 39 were also detected in our study (Table S2). However, due to the capability of the submarine to survey deeper waters (up to 330 m) 38 , reported four elasmobranch species that were not detected by our BRUVS (Table S2). Our study also reported more elasmobranch species at Caño Island than traditional underwater visual surveys 48 , which are often biased by divers' experience and limited by time, depth and weather conditions 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations